Losing Power : African Americans and Racial Polarization in Tennessee Politics - Franklin, Sekou M.; Block, Ray, Jr (Book collections on Project MUSE., 2020)
"Losing Power investigates the complex relationship between racial polarization, black political influence, and multiracial coalitions in Tennessee in the first decade of the twenty-first century. Sekou M. Franklin and Ray Block examine the divide in values, preferences, and voting behaviors between blacks and whites, contending that this racial divide is both one of the causes and one of the consequences of black Tennesseans' recent loss of political power. Tennessee has historically been considered more politically moderate and less racially conservative than the states of the Deep South. Yet in recent years and particularly since the mid- 2000s, Republicans have cemented their influence in the state. While Franklin and Block's analysis and methodology focus on state elections, political institutions, and public policy, Franklin and Block have also developed a conceptual framework for racial politics that goes beyond voting patterns to include elite-level discourse (issue framing), intrastate geographical divisions, social movements, and pressure from interest groups"--